The Impact of Employee Engagement and Work Placement on the Performance of UMKM Employees in Sambal Pecel Kediri - Iing Sri Hardiningrum; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardhana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is to find out how the performance of Sambal Pecel Kediri UMKM employees is influenced both partially and simultaneously by work engagement and placement. In this research, each member of the population is taken as a sample, which is known as a saturated sampling technique. A total of 30 employees from UMKM Sambal Pecel Kediri were research subjects. Observation, interviews, literature research, and questionnaires are the methods used to obtain data. To measure the data, a Likert scale was used. In addition, validity, reliability, classical assumptions, multiple linear regression analysis, t test, and F test were used. From the research results, the employee engagement variable has an influence but is not significant on the employee performance variable. The work placement variable has a partial and significant influence on the employee performance variable. Simultaneous test results show that employee engagement and work placement variables simultaneously influence employee performance variables. This is known from the results of the F test with a sig value of 0.000 (0.000<0.05).